Metode Simple Additive Weighting untuk Penentu Peringkat Variabel Kepuasan Konsumen pada Layanan Jasa - Budi, Setyo; Setiawan, Aries; Widjajanto, Budi; Kurniawan, Achmad Wahid (Teknik Informatika Universitas Pamulang, 2021)
The level of service in an agency is a supporter of the survival of an agency. consumer goals that arise from good service quality, are believed to be the main factors of business success. The indicator of the level of customer satisfaction with service quality is when consumers get maximum results from a desired need. Consumer measurements can be seen from the results of the buyer's assessment given by the service manager, and services in the form of consumers which result in goods or services being used as drivers. The method that will be used in the process of ranking consumer satisfaction variables in this study is Simple Additive Weighting. This method has a work order sequence by determining the weight value of each variable, then the ranking process by determining the best variable from the consumer satisfaction variable. The final result of this research is the ranking of consumer satisfaction variables from the highest to the lowest using Simple Additive Weighting to obtain an accuracy rate of 90%. The variable